IMPLEMENTASI KEBIJAKAN PEMBANGUNAN PASAR SAYUR “DARA JUANTI” DI KELURAHAN KAPUAS KIRI HULU KECAMATAN SINTANG KABUPATEN SINTANG - Halisya Ayunhir E.42008026 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
Skipsi writing is intended to describe the implementation of policy of development “Dara Juanti” vegetable market. This title is taken by issue of “Dara Juanti” vegetable market that has been long estabilized, but is uses unmaximal. This research used a qualitative analysis. This research used three stage are data collection, data analysis and conclusion. The research located at “Dara Juanti”vegetable market at Kapuas Kiri hulu village. Research subject is Sintang Government that associated with managing market, traders and people who life in around the market. The conclusion in this research is ineffectiveness of the management of market by the factors. In addition it is to necessary to review by Sintang government associated of market development policy for future continuation.Keyword : policy, implementation, government